The freedom of the protégés : sovereigns, ministers and civil servants of the Moroccan and Tunisian monarchies under French protectorate (1881-1956) - (:unkn) unknown (My University, 2019)
The Beylical and Cherifian monarchies were maintained by France when its protectorate was established in Tunisia (1881) and Morocco (1912). This dissertation intends to write the history of their political institutions and civil servants facing colonial administrations by explaining how the monarchies reacted to the colonial presence. It relies on the association of two corpuses. The first, a classic one, combines colonial sources and legal documentation to understand the protectorate as an object of administrative law. The second, more original, is composed of archives in Arabic produced by the sovereigns, ministers and servants of both countries. The combination of sources helps to understand how two polycentric monarchies were recomposed under colonial domination. This work thus shows that Moroccan and Tunisian actors were the main authors of the reform of the monarchy which is rejected by the colonial authorities. Its main hypothesis is that the survival of autonomous public services was enabled by the mosaic nature of the monarchies. Leaning on powerful public services, the Moroccan and Tunisian monarchs and servants were able to oppose the colonial authority with a progressive intensity until independence. This work helps to rethink the limits of the "State" in the North African context by highlighting administrations that have hitherto been ignored by colonial sources. It also feeds the comparative history between a triumphing monarchy in Morocco and another that disappeared in Tunisia in the first year of independence.
Keywords: African Research